S_8-module structures of anti-commutative algebra - Ydyrys, Abdibek (Journal of Emerging Technologies and Computing, 2024)
An algebra with identity ab = −ba is called anti-commutativealgebra. In this work we study S8-module structures of free anti-commutativealgebra of degree 8.